Akt and mTOR in B Cell Activation and Differentiation - Fruman, David A.; Limon, Jose J. (Frontiers in Immunology, 2012)
Activation of phosphoinositide 3-kinase (PI3K) is required for B cell proliferation and survival. PI3K signaling also controls key aspects of B cell differentiation. Upon engagement of the B cell receptor (BCR), PI3K activation promotes Ca2+ mobilization and activation of NFκB-dependent transcription, events which are essential for B cell proliferation. PI3K also initiates a distinct signaling pathway involving the Akt and mTOR serine/threonine kinases. It has been generally assumed that activation of Akt and mTOR downstream of PI3K is essential for B cell function. However, Akt and mTOR have complex roles in B cell fate decisions and suppression of this pathway can enhance certain B cell responses while repressing others. In this review we will discuss genetic and pharmacological studies of Akt and mTOR function in normal B cells, and in malignancies of B cell origin.